Analisis Kesulitan Siswa Dalam Pemecahan Masalah Matematika - Ruhyana Ruhyana (STMIK Mardira Indonesia, Bandung, 2016)
This article is an analysis of the test results about mathematical problem solving 6th grade elementary school students. The analysis aimed to find out the kinds of difficulties, causes difficulties, and how the handling of student difficulties in solving mathematical problems. From the analysis, teachers are expected to be able to anticipate what factors can make obstacles for students to work on the problems of mathematical problem solving. Keywords: mathematical problem solving.